An Appraisal of the Potential of Sequestering Carbon through Pomegranate Orchards in India - Arkalgud, Ganeshamurthy Nanjundaiah; Thimmasamudram Raghavareddy Rupa; Laxman Ramanna Hunashikatti; Sipra Mohapatra (Annals of Arid Zone, 2024)
Pomegranate is an important arid and semi-arid fruit crop of Indian origin. Land use change from agriculture to pomegranate orchards not only enhances farmers’ income but also helps in sequestering carbon and provides additional ecosystem services. Assessing carbon stocks and stock changes in fruit orchards is crucial under the United Nations Framework Convention on Climate Change and the Kyoto Protocol. In this context, we conducted a study to estimate carbon stocks in pomegranate orchards in India. We developed an exclusive allometric equation to estimate pomegranate tree biomass and collected extensive samples of trees, litter, weeds, and soil. We grouped pomegranate-growing areas by similarity in variety, soil, and climate, and then calculated the carbon held in these pools. Finally, we computed the carbon sequestered by pomegranates per hectare, providing valuable insights for climate change mitigation efforts. The national-level carbon storage in pomegranate orchards was then computed by multiplying the area occupied by pomegranate in these regions by the amount of carbon sequestered in one ha of land. Nearly 42.49 mt of carbon is sequestered in the pomegranate orchards of the country with 18.42 mt (43.36% of the total CS) stored in tree biomass and 24.1 mt (56.71% of the total CS) stored in soil. This study underscores the important role of pomegranate orchards in India, not only as a lucrative agro-economic venture for farmers but also as a significant contributor to carbon sequestration and overall ecosystem services. Such insights are essential for guiding sustainable land use practices and aligning agricultural efforts with global climate change mitigation strategies.